Travel-associated sexually transmitted infections: an observational cross-sectional study of the GeoSentinel surveillance database - Matteelli, Alberto; Schlagenhauf, Patricia; Carvalho, Anna CC; Weld, Leisa; Davis, Xiaohong M; Wilder-Smith, Annelies; Barnett, Elizabeth D; Parola, Philippe; Pandey, Prativa; Han, Pauline; Castelli, Francesco (The lancet. Infectious diseases, 2013)
Background - Travel is thought to be a risk factor for the acquisition of sexually transmitted infections (STIs), but no multicentre analyses have been done. We aimed to describe the range of diseases and the demographic and geographical factors associated with the acquisition of travel-related STIs through analysis of the data gathered by GeoSentinel travel medicine clinics worldwide. - Methods - We gathered data from ill travellers visiting GeoSentinel clinics worldwide between June 1, 1996, and Nov 30, 2010, and analysed them to identify STIs in three clinical settings: after travel, during travel, or immigration travel. We calculated proportionate morbidity for each of the three traveller groups and did logistic regression to assess the association between STIs and demographic, geographical, and travel variables. - Findings - Our final analysis was of 112 180 ill travellers—64 335 patients seen after travel, 38 287 patients seen during travel, and 9558 immigrant patients. 974 patients (0·9%) had diagnoses of STIs, and 1001 STIs were diagnosed. The proportionate STI morbidities were 6·6, 10·2, and 16·8 per 1000 travellers in the three groups, respectively. STIs varied substantially according to the traveller category. The most common STI diagnoses were non-gonococcal or unspecified urethritis (30·2%) and acute HIV infection (27·6%) in patients seen after travel; non-gonococcal or unspecified urethritis (21·1%), epididymitis (15·2%), and cervicitis (12·3%) in patients seen during travel; and syphilis in immigrant travellers (67·8%). In ill travellers seen after travel, significant associations were noted between diagnosis of STIs and male sex, travelling to visit friends or relatives, travel duration of less than 1 month, and not having pretravel health consultations. - Interpretation - The range of STIs varies substantially according to traveller category. STI preventive strategies should be particularly targeted at men and travellers visiting friends or relatives. Our data suggest target groups for pretravel interventions and should assist in post-travel screening and decision making. - Funding - US Centers for Disease Control and Prevention, and International Society of Travel Medicine.